Learning to fill the labor niche: Filipino nursing graduates and the risk of the migration trap - ORTIGA, Yasmin Y. (Institutional Knowledge at Singapore Management University, 2018)
Overseas recruitment has become a common strategy in filling nurse shortages within U.S. health institutions, sparking the proliferation of nursing programs in the Philippines. Export-oriented education exacerbates a mismatch, however, between available jobs (in both the Philippines and the United States) and the number of nursing graduates, thus increasing joblessness and underemployment among Filipino youth. Pursing higher education as a means to migrate also puts Filipino students at risk of getting caught in a migration trap, where prospective migrants obtain credentials for overseas work yet cannot leave when labor demands or immigration policies change. Such problems highlight the complicated impact of immigrant labor niches in places like the United States on developing nations, beyond the brain drain narratives that dominate academic and policy discussions.